Configuration of self-organizing informality: socio-spatial dynamic in favelas - Loureiro, V. (2017)
This paper aims to discuss on spatial patterns found in favelas throughout di erent cities worldwide, as they seem to reproduce similar con gurations and urban dynamics despite its diverse local contexts. The purpose is to explore these patterns in order to understand its social behaviour and address urban informality issues through it. To see how resilience seems to be inherent to such spaces, that grow vibrant, complex and dynamic global structures emerging and self-organizing from segregation in city space. It pursues the acknowledgement of structural morphological patterns of informality production, those genotypic characteristics that seem to be independent on culture, and might be representative of these social patterns commonly observed worldwide. Favela is observed in this study as a complex, self-organized entity, whose contrast to o cial city relies on its “bottom up” structure. It tends to follow natural rules of organization instead of formal urban strategies. Space Syntax (Hillier and Hanson, 1984) is the theoretical and methodological approach applied, through which it is possible to investigate these peculiar spatial patterns in favela, comparing several cases in Latin America, Africa and Asia. The analyses are based on axial and segment maps. Investigated variables are connectivity, local and global integration, mean depth, synergy, intelligibility, angular Choice, number and length of axes, and number and length of segments, compactness, normalized angular integration and choice for segment comparison. Findings show favela as an entity that maximises use and space into strong fragmented spatial structures, which provides the labyrinthic perception of users, but also accentuates spatial hierarchy. Topography is critical to the understanding of favela’s performance. The more accentuated, the more fragmented, labyrinthic and endogenous. Nevertheless, most analysed favelas locate in at areas and, therefore, present a tendency to better articulate with the surroundings, resulting in a softer in- and-out transition. Such topological performance seems better than Brazilian cities (Medeiros, 2013), which points out favela’s organizing structure as a possible model that could be adopted to re ne the con gurational performance of cities.